Colaboração premiada aplicada ao procedimento do Tribunal do Júri - Carvalho, Márcio Augusto Friggi de (2021)
The present work has the main objective of indicating possible paths for the application of the institute of the collaboration awarded in the procedure of the Court of the Jury. With the advent of disruptive technologies, the confrontation of modern crime started to demand the remodeling of the punitive apparatus to match the new challenges and the complexity of the network world. In fact, if in the past the dynamics of facts were easily reproduced in criminal proceedings with evidence of a testimonial, documentary and expert nature, with changes in social relations and in the face of new forms of communication, the criminal was also equipped with capable technical equipment. to increase the logistics of the crime and to greatly facilitate the criminal chain in increasingly complex structures of parallel power. In this context, the pressed collaboration emerges as an important instrument not only for the solution of white collar crimes, an environment in which it gained muscle in Brazil, but also in criminal demands related to the proceedings of the Jury Court, such as the mercenary murder and the groups of extermination. However, it is true that the application of the institute in question to the special procedure for intentional crimes against life poses significant problems and is difficult to solve from a procedural point of view. In addition, it is necessary to carefully assess the extent of spaces for consensus on crimes within the jurisdiction of the Jury before the axiological supremacy of human life in the criminal protection system. This is the proposal of the work: to highlight the main issues related to possible application limits and the possible adaptation of the tool in comparison with the procedure of the Popular Court in order to propose the solutions that may prove to be more appropriate